Effect of Z-Fiber® pinning on the mechanical properties of carbon fibre/epoxy composites - Troulis, Emmanouil (Cranfield University, 2003)
This study investigates the effects of Z-pinning on the delamination performance in opening and shear loading modes in woven fabric reinforced / epoxy composite materials, as well as the effects of friction between specimen crack faces and the Z-pin failure mechanisms involved in mode II delamination. Mode I and mode II delamination tests are carried out on Z-pinned unidirectional (UD) and woven laminates. Both UD and woven laminates exhibit enhanced delamination resistance and crack propagation stability through Z-pinning. The effects of various structural and Z-pin parameters on the mode I and mode II delamination behaviour are separately assessed. The 4ENF testing configuration is deemed as the appropriate mode II configuration for the testing of Z-pinned laminates. A new basic friction rig is used to measure the friction coefficient between crack faces in woven laminates. An additional friction effect attributed to fibre architecture is identified. A specially designed delamination specimen is used to overcome the difficulty of accurately measuring crack propagation in Z-pinned woven fabric materials and aid data reduction using the available analytical methods. The failure mechanisms involved in the mode II delamination of Z-pinned laminates have been investigated with the implementation of a new test. Z-pins fail under shear loading through a combination of resin crushing, laminate fibre breakage, pin shear, pin bending and pin pullout. The balance of the failure mechanisms is shown to be a function of the crack opening constraint, material type, stacking sequence, Z-pin angle and insertion depth to Z-pin diameter ratio. Z-pin and material parameters influencing Z-pinning quality are identified, categorised and quantified. The importance of controlling Z-pin insertion depth is underlined and updated manufacturing procedures are proposed. Partial pinning appears as an advantageous alternative. A reduction in in-plane stiffness and in-plane strength in UD and woven fabric composites is measured, whilst no significant change of in-plane shear stiffness of UD materials is observed. A reduction in the fibre volume fraction is the single most important parameter affecting the in-plane stiffness. The performance of a Z-pinned sub-structural component is investigated. Enhanced loading carrying capacity and damage tolerance is achieved through Z-pinning.
Keywords: delamination; unidirectional laminates; woven laminates; Z-pinning